Kansei evaluation of universal series bus (USB) charging cable designs - Abdillah, Muhamad Arif; Abd Latif, Mohd Arif Hafizi; Adnan, Ammar; Mat Hasan, Mohd Raziff; Sidek, Atiah Abdullah; Abdul Hamid, Abd. Malek (Malaysian Ministry of Higher Education, 2018)
Moving towards Industry 4.0, the use of Universal Serial Bus (USB) charging cable is a need among the users of smartphones whether android, iPhone, or others. Currently, many third party manufacturers produce USB charging cable with their own brand to fulfil the demand. However, the lifetime, design, and function of USB charging cable somehow may not meet user expectations. In the competitive market, it is important to know what are the user preferences regarding the existing USB charging cable design in the market especially in Malaysia. The objective of this study is to investigate affective aspect of USB charging cable perceived by the users and how they can be relating to product specifications. A survey at 30 stores around Klang Valley was conducted to find information regarding the current USB charging product in market and three selected designs were chosen based on the popularity and suggested by the store personnel. Then the Kansei online survey was done, in which respond from 111 volunteers- 65 males and 46 females- age between 18 to 30 years old [mean = 23.33; SD =1.73] were collected using Google forms survey. The respondents were asked to rate the three-designs based on Kansei words given. The data was analyzed to find the mean scores for the three selected designs -Design A, Design B, and Design C- in this study. It was found that Design C [mean=3.62; S= 0.2511] are the most preferred design, followed by Design B [mean=3.58; SD= 0.1904] and Design A [mean=3.28; SD= 0.3213]. Then, one-way ANOVA model was utilized (SPSS Version 23), and the finding shows that the difference between the three selected designs were significant [F (23,6) = 4.211, p = 0.040]. Design C becomes most preferred compared to other design due to its futuristic appearance, lightweight to carry, and more pleasant to hold which were agreed by most respondents. As a result, the subsequent data may serve to prove informative guideline for USB charging cable manufacture to design and produce the product that meet user preferences.